(untitled) (Journal of Engineering, 2013)
This research presents a model for surveying networks configuration which is designed and called a Computerized Integrated System for Triangulation Network Modeling (CISTNM). It focuses on the strength of figure as a concept then on estimating the relative error (RE) for the computed side (base line) triangulation element. The CISTNM can compute the maximum elevations of the highest obstacles of the line of sight, the observational signal tower height, the contribution of each triangulation station with their intervisibility test and analysis. The model is characterized by the flexibility to select either a single figure or a combined figures network option. Each option includes three other implicit options such as: triangles, quadrilaterals, and central-point figures (which is to be subdivided into: triangle; quadrilateral, and pentagon). The model also has the property of the diverse modes of display for the output results; i.e. the results can be displayed in the shape of TwoDimensional (2-D) and Three- Dimensional (3-D) representations. Visual Basic is the software depended as a main core in designing CISTNM to draw the suggested network in 2-D to display the network point positions and formations, and it can be linked with the available software such as ArcMap (GIS). The input data which is used as an application of the targeted geodetic surveying techniques (triangulation) is Chamchamal region as a case study in this research. The area lies in the north of Iraq. The results obtained after this application and verification, have proved that the CISTNM can perform the required task easily and accurately.